Pengembangan Modul Berbasis Education for Sustainable Development pada Konsep Ekologi untuk Siswa Kelas X SMA - Rahman, Aditya; Heryanti, Lucya Mega; Ekanara, Bambang (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2019)
This research aimed to develop a product and to find out its eligibility and students’s response of module based education for sustainable development (EfSD) on ecology concept for X grade students. Research and development (R&D) method with Dick & Carey model was used in this research. It consisted of 5 stages, that were Analysis, Planning, Development, Formative Evaluation, and Revision. Instrument validation was assessed by experts (concept, media and teachers). According to the result of expert assesment, the module earned score 94%. The score was included into very decent category. The score of students’s response was 84,4%. The score was included into very worth category. It can be concluded module based EfSD on ecology concept for X grade students was  very decent for learning material.